The legacies of two world wars : European societies in the twentieth century - Kettenacker, Lothar 1939- Hrsg (Berghahn, 2014)
Formerly CIP Uk. - Includes bibliographical references and index. - "Old Europe" and the legacy of two world wars / Lothar Kettenacker and Torsten Riotte -- Prevention or regulation of war? : the Hague peace conferences as a limited tool for reforming the international system before 1914 / Jost Dülffer -- "The spirit of 1914" : a critical examination of war enthusiasm in German society / Gerhard Hirschfeld -- Construction and deconstruction of the idea of French "war enthusiasm" in 1914 / Nicolas Beaupré -- The mood in Britain, 1914 / Hartmut von Pogge Strandmann -- The First World War in the history of the Weimar Republic / Gerd Krumreich -- Fascism and legacy of the Great War / Angelo Ventrone -- The French desire for peace and security in the 1920's / Jean-Claude Allain -- Britain in the wake in the Great War / Jay Winter -- Germany : war without public backing / Hans Mommsen -- The French entry into the war in September 1939 : between reluctans and resignation / Barbara Lambauer -- Great Britain : declaring war as a matter of honour / Lothar Kettenacker -- Disillusionment, pragmatism, indifference : German society after the "catastrophe" / Clemens Vollnhals -- The French after 1945 : difficulties and disappointments of an immediate post-war period / Fabrice Grenard -- Great Britain : remembering a just war (1945-1950) / Toby Haggith -- Italy after 1945 : war and peace, defeat and liberation / Gustavo Corni